(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The reward system in Islamic Educational institutions still faces a number of fundamental issues. This study aims to describe the concept, forms, and implementation of the reward system in Islamic educational institutions by integrating modern human resource management theories with Islamic values. This study uses a qualitative descriptive approach through a literature review, drawing data from journals published by google scholar, researchgate, garuda, and sinta, published between 2020-2025, related to Islamic education management. Data collection was conducted throught documentation, and data analysis was conducted using content analysis. The findings indicate that a fair and transparent Islamic-based reward system can improve teacher motivation, strengthen professional commitment, and create a productive and spiritually enriched work environment. However, its implementation still faces challenges, particularly limited funding, inconsistent policies, and insufficient managerial competence within Islamic educational institutions. Therefore, optimizing a reward system grounded in Islamic values and professional management principles is essential to achieve educator welfare and balanced educational quality in Islamic education